Influencer’s Trustworthiness for Car Purchase - Gabriele Faustine Hartawidjaja; Anna Amalyah Agus (PT Mattawang Mediatama Solution, 2023)
Determine the effect of trustworthiness, customer participation behaviour, customer citizenship behaviour, and expected brand value towards purchase intention in high involvement product. This research uses purposive sampling, quantitative approach and SEM-PLS method with the Smart-PLS version 4 software. All direct effects are proven as significant and affective, except for trustworthiness effect against customer participation behaviour, and customer participation behaviour against brand expected value. All mediation effects are not significant, except for expected brand value’s mediation variables which mediate trustworthiness with purchase intention. There is no moderation effect by para-social relationship between neither trustworthiness and customer participation behaviour, nor trustworthiness and customer citizenship behaviour. Novelty of this research can be found in the research object itself, which is influencer's influence on products' high involvement with independent trustworthiness as variable, where automotive influencer is used as research object. Moreover, this research is conducted in a different country than previous research. Building trust is one of the most important things in ensuring the success of customer citizenship behavior, by giving key updates via various social media or brand influencer. Brand owners could also increase their own involvement in exploring social media, one of the examples is by doing campaign to communicate and interact with customers, reviews, comments, and votes. Brand owners could also consider whether Fitra Eri is the most suitable automotive influencer to promote their brand, in accordance with their objectives. The conclusions taken from the research in another countries, cultures, or influencers cannot be generalized. Followers’ intention of following the influencer is not necessarily related with their purchase intention.